Ethnographic Study of School Culture in North Aceh District, Aceh Province (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to: 1) explore school culture, 2) describe the meaning of school culture, 3) describe school cultural values. This type of research is a qualitative research using an ethnographic approach. This research was conducted at Sawang 11 State Elementary School, North Aceh District. The informants of this research are school principals, teachers, education staff, and students. Data collection techniques include; observation, interview and documentation. Data analysis techniques include; 1) domain analysis, 2) taxonomic analysis, 3) componential analysis and, 4) cultural theme analysis. The results showed that first, the school culture developed at Sawang 11 Public Elementary School consisted of religious culture, literacy culture, adiwiyata culture and social culture. Second, the meaning of school culture at Sawang 11 Public Elementary School was character building and school quality improvement, third, the values ​​contained in the school culture include; the value of piety, the value of responsibility, the creative value, the independent value, the value of loving the environment, the value of beauty, the value of empathy and the value of togetherness/kinship.